The Alkynylative Difunctionalization of Alkenes - Huang, Jie; Chen, Zhi‐Min (Chemistry : a European journal, 2022)
Given alkynyl group is an important functional unit, a variety of efficient methods have been developed to construct alkynyl‐containing compounds. Among them, the alkynylative difunctionalization of alkenes is one of the most straightforward and efficient strategies for preparing these compounds and so has made great progress in recent years, including the catalytic asymmetric manner. However, there is no comprehensive review to summarize these studies. This review is aimed at comprehensively summarizing the alkynylative difunctionalization of alkenes, which is presented in terms of alkynylation‐initiated and alkynylation‐terminated difunctionalizations of alkenes. We hope that this review will help to encourage more researchers to further explore in this field. The alkynylative difunctionalization of alkenes is one of the most straightforward and efficient strategies for preparing useful alkynyl‐containing compounds and so has made great progress in recent years. This review comprehensively summarized the alkynylative difunctionalization of alkenes. For more information, see the Review by J. Huang and Z.‐M. Chen (DOI: 10.1002/chem.202201519).